2011
DOI: 10.1093/brain/awr075
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dopamine therapy on ventral and dorsal striatum-mediated cognition in Parkinson’s disease: support from functional MRI

Abstract: The central aim of our study was to elucidate functions mediated by the ventral and dorsal striatum, respectively, to better understand the cognitive effects of dopamine replacement in Parkinson's disease. We proposed that the ventral striatum underlies general learning of stimulus associations, whereas the dorsal striatum promotes integration of various influences on selecting. In Parkinson's disease, dopamine depletion is substantially less notable in the ventral relative to the dorsal striatum, and therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
95
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 107 publications
22
95
0
Order By: Relevance
“…Siepel et al [26] reported that reduction of striatal tracer binding at DAT-Scan imaging was associated with executive but not visual-spatial or memory dysfunctions in early PD patients. Pathophysiological, neuropathologic and neuroimaging studies confirmed the presence of cognitive alterations in PD patients devoid of cortical pathology [27]- [33]. These findings, therefore, suggest that the basal ganglia dysfunction driven by nigrostriatal dopamine depletion may produce cognitive symptoms per se.…”
Section: Cognitive Impairment In Pdsupporting
confidence: 52%
“…Siepel et al [26] reported that reduction of striatal tracer binding at DAT-Scan imaging was associated with executive but not visual-spatial or memory dysfunctions in early PD patients. Pathophysiological, neuropathologic and neuroimaging studies confirmed the presence of cognitive alterations in PD patients devoid of cortical pathology [27]- [33]. These findings, therefore, suggest that the basal ganglia dysfunction driven by nigrostriatal dopamine depletion may produce cognitive symptoms per se.…”
Section: Cognitive Impairment In Pdsupporting
confidence: 52%
“…Recently, it has been suggested that the ventral striatum is important for the general learning of stimulus-response associations, whereas the dorsal striatum promotes integration of various influences on action selection (MacDonald et al, 2011). Because dopamine depletion is not uniform but more pronounced in the dorsal striatum compared with the ventral striatum in the early stages of PD (Bernheimer et al, 1973;Frey et al, 1996;Kwak et al, 2010), it may not be surprising that we specifically observed a deficit in trial-by-trial AR that was ameliorated by dopamine medication.…”
Section: Discussionmentioning
confidence: 62%
“…Specifically, there is a more pronounced reduction of dopamine in the dorsal than in the ventral striatum (Kish et al, 1988). Therefore, therapies that restore dopamine level in the dorsal striatum result in dopamine 'overdose' in the ventral striatum, which may lead to impaired performance on some cognitive tasks (Gotham et al, 1988;Cools et al, 2001Cools et al, , 2003Shohamy et al, 2006;Jahanshahi et al, 2010;MacDonald et al, 2011) and in some cases psychotic symptoms, including hallucinations and delusions (McGowan et al, 2004;Mehler-Wex et al, 2006;Maia and Frank, 2011). At the same time, there is evidence that dopaminergic therapy enhances learning from reward signals and decreases learning from punishment signals in PD (Frank et al, 2004(Frank et al, , 2007Cools et al, 2006;Bódi et al, 2009;Graef et al, 2010;Kobayakawa et al, 2010), and the ventral striatum has a crucial role in reinforcement learning (Yin and Knowlton, 2006).…”
Section: Introductionmentioning
confidence: 99%